The Relevance of Gynecologic Oncologists to Provide High-Quality of Care to Women with Gynecological Cancer - Minig, Lucas; Padilla-Iserte, Pablo; Zorrero, Cristina (Frontiers in Oncology, 2016)
Gynecologic oncologists have an essential role to treat women with gynecological cancer. It has been demonstrated that specialized physicians who work in multidisciplinary teams to treat women with gynecological cancers are able to obtain the best clinical and oncological outcomes. However, the access to gynecologic oncologists for women with suspected gynecological cancer is scarce. Therefore, this review analyzes the importance of a specialized care of women with ovarian, cervical, endometrial and ovarian cancer. In addition, the roles of gynecologic oncologists who offer fertility-sparing treatment as well as their role to assist general gynecologists and obstetricians are also reviewed.